ISOLASI DAN IDENTIFIKASI Streptomyces sp. PADA RHIZOSFER TANAMAN PISANG (Musa paradiasica) DI DESA PENDEM JEMBRANA BALI - Kawuri, Retno (Metamorfosa: Journal of Biological Sciences, 2016)
Pendem village in Jembrana regency is one of the banana plantation in Bali. Now a days banana plants were attack  by  bacterial wilt disease   with the symptoms of wilting plants, brown spots on the vessel banana stems and fruit to rot and dry. Control of use of chemical fertilizers can cause bad impact on environment and also can not control the disease. Streptomyces bacteria are bacteria that are capable of producing enzymes and antibiotics that can be used as biocontrol agents of several diseases in plants. The purpose of this research is to isolate and identify the bacteria  Streptomyces  from  rhizosphere  of  banana  plants  without  symptoms  in  the  village Pendem Jembrana regency. The method of isolation of Streptomyces using Platting method, Streptomyces isolated from soil rhizosphere of banana plants without symptoms or health plant. Soil was taken by digging near rooting bananas plant about 15 cm from the ground and and the sample was growth on media Humic Vitamin Agar (HVA) and Yeast Extract Malt Agar (ISP4). Identification macros-copically and microscopically and biochemical test using determination key book guide to the Classification and Identification of the Actinomycetes and Their antibiotics of Lechevalier and Waksman (1973). Result showed it was found 9 Streptomyces isolate;   Streptomyces sp.1, Streptomyces sp. 2, Streptomyces sp.3, sp. 4 Streptomyces , Streptomyces sp.5 sp.6, Streptomyces sp 7, Streptomyces sp.8 and Streptomyces sp.9. Nine isolates of Streptomyce s sp. will be tested against the bacteria Ralstonia solanacearum ,the bacteria that causes bacterial wilt disease.
Keywords: Streptomyces sp., rhizosphere, banana plants, identification